Hip-hop, identity, and conflict: Practices and transformations of a metropolitan culture - Benvenga, Luca (Frontiers in Sociology, 2022)
In this paper, I expose how it is possible to investigate the hip-hop culture on three levels of analysis – historical, semiotic and phenomenological – precisely as theorized by Phil Cohen (1997) for his study on modern subcultures. The analysis will focus on the hip-hop of the beginning, since the middle of the Seventies and Eighties in the U.S.A., but then it will broaden to a reflection on its diffusion and re-invented, with particular reference to the interactions with the globalization and the changes occurred in contemporary metropolis. In this sense, considering hip-hop as a subculture in the following pages I reflect a) on the origin of rap music, its interrelation with the Afro-American culture and the concept of blackness which it conveys. Subsequently I clarify b) that the art of writing, in the form of Tag, and break-dance, have certificated the presence of young people from the U.S. outskirts, and then the passage to a precise historical moment. Finally, I try to demonstrate c) that today a different dimension of hip-hop is implemented, whose features have changed in parallel with the transformations which have affected the metropolis and the youth cultures. These last one are increasingly hybrid and involved in a recreational, market system, where the changing nature of hip-hop allows: its enormous success, with the domain of the musical market and other assimilation processes, such as clothing, which have contributed to its mutation in a global culture; some margins of autonomy.